Strategic Management / International Edition: Second Edition - Dess Gregory G; Miller Alex (Mcgraw Hill Publishing Company, 1996)
Preface, Strategic Analysis, The Strategic Management Imperative, External Analysis, Internal Analysis, Strategy Formulation, Business-Level Strategy, Operations-Level Strategy, Corporate-Level Strategy, International-Level Strategy, Strategy Implementation, The Challenge of Strategy Implementation, Leadership for Organizational Learning, Context Levers, System Levers, Action Levers, Cases, Indexes.
Preface, Strategic Analysis, The Strategic Management Imperative, External Analysis, Internal Analysis, Strategy Formulation, Business-Level Strategy, Operations-Level Strategy, Corporate-Level Strategy, International-Level Strategy, Strategy Implementation, The Challenge of Strategy Implementation, Leadership for Organizational Learning, Context Levers, System Levers, Action Levers, Cases, Indexes.